El rol preventivo de las consultoras ambientales y su importancia en el proceso de evaluación del impacto ambiental: Actualización de últimos cambios normativos - Queirolo Romero, Ana Paula (2018)
In Environmental Law, the regulation of the consultants and the regime to which they are subject is questioned. However, those who question it have not analyzed the fundamental role that they fulfill within the procedure that implies an environmental certification. Through this article, the author aims to explain the evolution of environmental consultants and demonstrate their role within the economic regime in Peru.